KONSEP KEADILAN DALAM QS. AL-MAIDAH AYAT 8 DAN AYAT 42 (Studi Komparatif Tafsir al-Manar dan Tafsir al-Azhar) - Fauzi Fathur Rosi; Puji Wage Astuti (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2025)
In Islam, justice is the foundation of life in the social order. When deciding something, both in personal life and in interacting with others, justice must be prioritized. This study will discuss the concept of justice according to Muhammad Rashid Ridha and Buya Hamka and how the similarities and differences between the two commentators are regarding the characteristics of their interpretations. The research method used is (library research), in data collection using the documentation method. The results of this study are that Rashid Ridha in Tafsir al-Manar argues that justice is a basic value that covers all aspects of life, both social relations and relations with Allah SWT. Meanwhile, Abdul Malik Karim Amrullah in Tafsir al-Azhar emphasizes that justice is a moral obligation that must be carried out according to the guidance of the Qur'an. In terms of the characteristics of interpretation, Rashid Ridha emphasizes justice more in the legal and policy aspects, while Abdul Malik Karim Amrullah focuses on the moral aspects, individual character, and psychological impacts of justice.